1990
DOI: 10.1111/j.2044-8279.1990.tb00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement in the Teaching of Reading: A Comparison of Hearing Reading, Paired Reading, Pause, Prompt, Praise, and Direct Instruction Methods

Abstract: SUMMARY.The parents of 40 children in two grade 1 classrooms were randomly assigned to receive brief training in one of four instructional methods for helping their child to read or to hear their children read at home. The tutoring methods were Hearing Reading, Paired Reading, Pause, Prompt, Praise, and Direct Instruction. The results showed that the use of the additional instructional strategies included in the Direct Instruction and Paired Reading tutoring methods led to faster progress by the children recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 4 publications
1
37
0
Order By: Relevance
“…The PR method teaches parents to read simultaneously with their child, and to support the child when he/she is reading independently (Toomey, 1993). Leach and Siddall (1990) compared the effects of several different programs that involved parents and their beginning readers. Their study compared PPP, PR, hearing reading (parents listen to their children read), and Direct Instruction (parents are provided with scripted lessons and books to use with children).…”
Section: Integrity Of Parent Tutoring Practicesmentioning
confidence: 99%
“…The PR method teaches parents to read simultaneously with their child, and to support the child when he/she is reading independently (Toomey, 1993). Leach and Siddall (1990) compared the effects of several different programs that involved parents and their beginning readers. Their study compared PPP, PR, hearing reading (parents listen to their children read), and Direct Instruction (parents are provided with scripted lessons and books to use with children).…”
Section: Integrity Of Parent Tutoring Practicesmentioning
confidence: 99%
“…There are, however, examples in which parents and other non-teachers have taken the lead role with great success (Baker, Gersten & Keating, 2000;Fitzgerald, 2001;Kraft, Findlay, Major, Gilberts & Hofmeister, 2001; Leach & Siddall, 1990). Kraft et al (2001) evaluated the reading skills of Kindergarten level children following a home based beginning reading program before which parents undertook two hours of instructional training.…”
mentioning
confidence: 99%
“…The approach is based upon the work of Siegfried Engelmann, who achieved significant success in reading instruction with earlier programs, such as Distar Reading, Reading Mastery, and Corrective Reading (Adams & Engelmann, 1996). These are teacher presented group programs; however, one parent based direct instruction program called Teach Your Child to Read in 100 Easy Lessons (Engelmann, Haddox & Bruner, 1983) has been published, and has received some empirical validation (Hempenstall, 2002;Leach & Siddall, 1990). It was a parent version developed out of the Reading Mastery classroom program.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leach and Siddall(1990), like Wheldall and Mettem (1985), used analyses of covariance and planned comparisons to compare their groups. Unlike Wheldall and Mettem (1985), however, Leach and Siddall(l990) found that on measures of both reading accuracy and reading comprehension, Pause, Prompt and Praise was one of the least effective procedures.…”
Section: ) Would Have Us Believementioning
confidence: 99%